George Redington papers - Redington, George, 1798-1850.; Redington, James, 1810-1891.; Sons of Temperance of North America. Waddington Division, No. 299 (Waddington, N.Y.)
Correspondence, legal documents, business records, and ledgers relating to Redington's lumber mills and business activities in the Waddington-Ogdensburg, N.Y., area. Includes papers of his brother James and other Redington family members; papers of the Ogden and Parish (Parrish) families of Ogdensburg; and records of Waddington Division, No. 299, of the Sons of Temperance of North America.
Lawyer, legislator, judge, businessman, and land agent of New York.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ogden family; Parrish family; Redington family; Lumber trade -- New York (State); New York (State) -- Commerce; Ogdensburg (N.Y.) -- Commerce; Waddington (N.Y.) -- Commerce; Businessmen; Jurists; Land agents; Lawyers; Legislators -- New York (State)